2020
DOI: 10.1111/jdv.16766
|View full text |Cite
|
Sign up to set email alerts
|

The predictive and prognostic significance of cell‐free DNA concentration in melanoma

Abstract: Background Melanoma is the leading cause of skin cancer‐related deaths worldwide. While there have been significant improvements in the treatment of advanced melanoma in the past decade, biomarker development lagged behind. Objectives The majority of liquid biopsy biomarkers rely on the analyses of oncogenic mutations; however, about 20% of melanoma patients are wild type. Therefore, validation of universal predictive and prognostic biomarkers is urgently needed. Methods We analysed plasma samples in a discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
(62 reference statements)
1
6
1
Order By: Relevance
“…In agreement with the literature, 14,15 cfDNA yield varied widely between cancer patients, tumor types, and tumor burden. The range of plasma volumes was 2.4mL to 6mL with a median of 5mL.…”
Section: Plasma Cfdna Yield In a Pan-cancer Cohortsupporting
confidence: 90%
“…In agreement with the literature, 14,15 cfDNA yield varied widely between cancer patients, tumor types, and tumor burden. The range of plasma volumes was 2.4mL to 6mL with a median of 5mL.…”
Section: Plasma Cfdna Yield In a Pan-cancer Cohortsupporting
confidence: 90%
“…Currently, 22 clinical trials are registered in the ClinicalTrials.gov database aiming to study either the prognostic value of BRAF-or NRAF-mutated ctDNAs, their modulation during treatments and the standardization of methods for ctDNA quantification and mutation detection. Interestingly, although total cfDNA cannot be considered a melanomaspecific biomarker, Varaljai et al in 2020, demonstrated that high levels of cfDNA can provide information on tumor load, risk of progression and risk of death irrespective of the tumor genotype [235].…”
Section: Melanomamentioning
confidence: 99%
“…Finally, ctDNA can be applied for non-typical melanoma mutation detection (wild-type patients, constituting ca. 20% of all melanoma cases) [ 136 ] and tumor-specific gene methylation detection and be used for early diagnosis of melanoma [ 137 ]. Several study results showed that the presence of hypermethylation in the promoter region of PTEN , TFPI2 , RARB2 , MGMT , and RASSF1A genes in ctDNA enabled differentiation of melanoma patients from healthy individuals [ 138 , 139 , 140 ], with elevated levels of methylated RASSF1A ctDNA more attributed to metastatic cases compared to early-stage melanoma [ 140 ].…”
Section: Clinical Relevance Of Liquid Biopsy In Melanomamentioning
confidence: 99%